An Introduction to management science : quantitative approaches to decision marketing - Anderson, David R. 1941- (David Ray) (South-Western ; Cengage Learning, 2011)
Provide your students with a sound conceptual understanding of the role that management science plays in the decision-making process with the latest edition of the book that has defined today's management science course: Anderson/Sweeney/Williams/Camm/Martin's An Introduction to Management Science: Quantitative Approaches to Decision Making, Revised 13th Edition. The trusted market leader for more than two decades, the new edition of this text now reflects the latest developments in Microsoft Office Excel 2010. All data sets, applications and screen visuals throughout this REVISED 13th Edition reflect the details of Excel 2010 to accurately prepare your students to work with today's latest spreadsheet tools. The authors continue to provide unwavering accuracy with the book's proven applications-oriented approach and timely, powerful examples. The book's hallmark problem-scenario approach introduces each quantitative technique within an applications setting. Students must apply the management science model to generate solutions and recommendations for management. A comprehensive support package offers all the written and online time-saving support you need with trusted solutions written by the text authors to ensure accuracy. Students gain an understanding of today's most useful software applications with premium online content, including online chapters, LINGO software and Excel add-ins. Students even receive a copy of the popular Microsoft Project Professional 2010 on the text's accompanying CD. Trust the world leader An Introduction to Management Science: Quantitative Approaches to Decision Making, Revised 13th Edition to provide the support your course and today's students need. The Student Essential Site PAC (Printed Access Card) that comes with the new book includes: Case Files, Example Files, Problem Files, Tutorials, Solvertable, Palisade DecisionTools (StatTools), Excel Tutorial. - Publisher.